Retrograde washout of prepump LVAD thrombosis in a patient on HeartWare™ support - Elbayomi, Mohamed; Weyand, Michael; Heim, Christian; Steger, Katrin; Tandler, Rene (Journal of Cardiac Surgery, 2022)
The success of the left ventricular assist device (LVAD) as a treatment for terminal left-side heart failure is still restrained by some severe complications associated with mechanical circulatory support. Pump thrombus still affects many patients. It is associated with high morbidity and mortality. The therapeutic options include augmentation of anticoagulation and antiplatelet medication, intravenous or catheter-guided thrombolysis, and pump exchange. Heart transplantation would be a desirable option in this population, but unfortunately, it is only theoretical given the increasing number of LVAD implants and decreasing number of organ donors. A retrograde washout maneuver may be a treatment option in prepump thrombosis in selected patients. Therefore, the decision should be made on an individual basis after balancing the risks and benefits of different treatment approaches. In this context, we report a case of retrograde washout of prepump thrombus in a patient who has been on HeartWare™ support for more than 3 years, with a successful bailout strategy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Medtronic/HeartWare HVAD; peripheral thromboembolism; retrograde washout; thrombus; ventricular assist device